View of intra-city differences and its position in explaining the factors affecting the identity of urban space using logistic and differentiation methods. Case study: West and East regions of Mashhad - mostafa amirfakhriyan (تحقیقات کاربردی علوم جغرافیایی)
Identity, as a complex concept, influenced by a variety of factors, makes one thing distinct and unique. Meanwhile, the characteristics of the environment, habits, worldview, cultural characteristics, etc., have a growing influence on the formation of these indices of identity. In other words, this study seeks to investigate the hypothesis of the difference in attitudes of inhabitants of the eastern and western parts of Mashhad towards urban identity indices and, finally, whether the distinction is observable or not? The basis of this study is based on quantitative methods that have been used for research purposes, along with qualitative methods. The output of this discussion is to achieve the identity of the city and its classification according to the purpose of the study. But in the small part, the study method is based on the use of differentiation and logistic models to show the type and level of differences between the eastern and western parts of Mashhad. Based on this, the rank of indicators of urban identity components was obtained in the form of a questionnaire in two categories of eastern regions (regions 4, 5 and 6) and western regions (including 1, 9 and 11) from the residents' perspective. The completed questionnaires were entered into the statistical database and analyzed using statistical software such as Excel and Spas. Study shoes that: 1- Regarding the formic index, studies show that variables such as high buildings, traditional architecture and natural form of place are variables that cause segregation of residents of eastern and western parts of Mashhad. 2- The results in Function indices also indicate that variables of vibrant places, places with activities, boarding times, places with different uses, and safe places are meaningful. 3- Finally, regarding the semantic indices, the effective and differentiating variables in the eastern and western regions of Mashhad, including two variables of understanding the sense of pilgrimage and understanding the characteristics of Islamic culture. Accordingly, it can be said that the attitudes of residents of the studied areas are different from those related to the sense of pilgrimage and the characteristics of Islamic culture in their. the end